3D printing with SketchUp : real-world case studies to help you design models in SketchUp for 3D printing on anything ranging from the smallest desktop machines to the largest industrial 3D printers /: real-world case studies to help you design models in SketchUp for 3D printing on anything ranging from the smallest desktop machines to the largest industrial 3D printers. (2014) - Ritland, Marcus
No abstract available